Is it worthwhile to go beyond the local‐density approximation in subsystem density functional theory?. Issue 21 (11th December 2019) - Grimmel, Stephanie A.; Teodoro, Tiago Q.; Visscher, Lucas
Abstract: Frozen density embedding (FDE) theory is one of the major techniques aiming to bring modeling of extended chemical systems into the realm of high accuracy calculations. To improve its accuracy it is of interest to develop kinetic energy density functional approximations specifically for FDE applications. In the study reported here we focused on optimizing parameters of a generalized gradient approximation‐like kinetic energy functional with the purpose of better describing electron excitation energies. We found that our optimized parametrizations, named excPBE and excPBE‐3 (as these are derived from a Perdew‐Burke‐Ernzerhof‐like parametrization), could not yield improvements over available functionals when applied on a test set of systems designed to probe solvatochromic shifts. Moreover, as several different functionals yielded very similar errors to the simple local‐density approximation (LDA), it is questionable whether it is worthwhile to go beyond the LDA in this context. Abstract : Specific optimization of a generalized gradient approximation (GGA)‐like kinetic energy functional with the purpose of better describing solvatochromic shifts on electron excitation energies leads to limited improvement over existing functionals. Moreover, as several different functionals yield very similar errors as the simple local‐density approximation (LDA), it is questionable whether it is worthwhile to go beyond the LDA in this context.